Glucoselipid Biosurfactant Biosynthesis Operon of Rouxiella badensis DSM 100043T: Screening, Identification, and Heterologous Expression in Escherichia coli - Andre Fahriz Perdana Harahap; Chantal Treinen; Leonardo Joaquim Van Zyl; Wesley Trevor Williams; Jürgen Conrad; Jens Pfannstiel; Iris Klaiber; Jakob Grether; Eric Hiller; Maliheh Vahidinasab; Elvio Henrique Benatto Perino; Lars Lilge; et al. (Microorganisms, 2025)
Rouxiella badensis DSM 100043T had been previously proven to produce a novel glucoselipid biosurfactant which has a very low critical micelle concentration (CMC) as well as very good stability against a wide range of pH, temperature, and salinity. In this study, we performed a function-based library screening from a R. badensis DSM 100043T genome library to identify responsible genes for biosynthesis of this glucoselipid. The identified open reading frames (ORFs) were cloned into several constructs in Escherichia coli for gene permutation analysis and the individual products were analyzed using high-performance thin-layer chromatography (HPTLC). Products of interest from positive expression strains were purified and analyzed by liquid chromatography/electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS) and nuclear magnetic resonance (NMR) for further structure elucidation. Function-based screening of 5400 clones led to the identification of an operon containing three ORFs encoding acetyltransferase GlcA (ORF1), acyltransferase GlcB (ORF2), and phosphatase/HAD GlcC (ORF3). E. coli pCAT2, with all three ORFs, resulted in the production of identical R. badensis DSM 100043T glucosedilipid with Glu-C10:0-C12:1 as the main congener. ORF2-deletion strain E. coli pAFP1 primarily produced glucosemonolipids, with Glu-C10:0,3OH and Glu-C12:0 as the major congeners, predominantly esterified at the C-2 position of the glucose moiety. Furthermore, fed-batch bioreactor cultivation of E. coli pCAT2 using glucose as the carbon source yielded a maximum glucosedilipid titer of 2.34 g/L after 25 h of fermentation, which is 55-fold higher than that produced by batch cultivation of R. badensis DSM 100043T in the previous study.